Karo Traditional Food Inventory in the Design of Culinary Branding in Toba - Muhammad Zulfan; Muhammad Yunus (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2021)
This study has three research objectives,(1) Prepare a detailed inventory of traditional Toba foods which include: (a) Types of traditional foods (b) Traditional food processing methods, (c) Economic aspects and (d) Documentation, (2) Developing traditional food development alternatives and (3) designing Branding on traditional food in Toba District. The type of this research is survey research with descriptive method. The results Based on a survey conducted in Toba District identified a number of 4 types of traditional food. The main ingredients most widely used for making traditional food is Fish (80%), then other ingredients (20%). Toba traditional foods, based on the way of processing can be categorized into three, namely: (1) steamed, (2) fried, (3) and boiled. Based on interviews with resource persons and traditional food community figures in Toba, several alternative development that can be done are: Identification and Inventory of traditional food, Preparing the profile of traditional food in the area as food information and counseling and Promotion, Encouraging the development of traditional food centers with relevant agencies, private and community; Provision of soft loans for additional capital.